2011
DOI: 10.1016/j.immuni.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The Distal VH Gene Cluster of the Igh Locus Contains Distinct Regulatory Elements with Pax5 Transcription Factor-Dependent Activity in Pro-B Cells

Abstract: V(H)-DJ(H) recombination of the immunoglobulin heavy chain (Igh) locus is temporally and spatially controlled during early B cell development, and yet no regulatory elements other than the V(H) gene promoters have been identified throughout the entire V(H) gene cluster. Here, we discovered regulatory sequences that are interspersed in the distal V(H) gene region. These conserved repeat elements were characterized by the presence of Pax5 transcription factor-dependent active chromatin by binding of the regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
186
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(195 citation statements)
references
References 45 publications
8
186
0
1
Order By: Relevance
“…At Igh and Igk, CTCF sites are generally intergenic except for those in the proximal one-third of the V H array, which are downstream of V H RSSs; moreover, CTCF sites are not associated with the major Igh and Igk enhancer elements (25,26,(48)(49)(50). At these loci, CTCF promotes long-distance interactions between CTCFbinding elements (24)(25)(26), but these looping interactions appear primarily to restrict or insulate the activities of the major enhancer elements.…”
Section: Discussionmentioning
confidence: 99%
“…At Igh and Igk, CTCF sites are generally intergenic except for those in the proximal one-third of the V H array, which are downstream of V H RSSs; moreover, CTCF sites are not associated with the major Igh and Igk enhancer elements (25,26,(48)(49)(50). At these loci, CTCF promotes long-distance interactions between CTCFbinding elements (24)(25)(26), but these looping interactions appear primarily to restrict or insulate the activities of the major enhancer elements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that the level of Pax5 mRNA is twofold lower in YY1 −/− pro-B cells, and binding of Pax5 to the PAIR promoters also reduced. Because Pax5 is essential for antisense transcription from PAIR elements (19), this could also contribute to the reduction in PAIR-supported antisense transcription. In addition, we demonstrated that YY1 −/− pro-B cells showed greatly diminished interactions of PAIR elements with Eμ.…”
Section: Discussionmentioning
confidence: 99%
“…These 14 PAIR elements contain binding motifs for Pax5, CTCF, and E2A. Transcription from PAIR elements is dependent on the transcription factor Pax5, which only binds to these elements in pro-B cells (19). Data from our laboratory demonstrated that CTCF acts as negative regulator of transcription from PAIR elements because the knockdown of CTCF resulted in increased antisense transcription from PAIR elements in pro-B cells (15).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, in the Pillars article, Yancopoulos and Alt (8) foreshadowed a major issue that remains unresolved today: the identity of cis elements that drive V H -glt and presumably recombination of the complex V H cluster (8). Progress has been slow, but a recent report that certain mouse V H clusters have PAX5 target elements harboring intrinsic enhancer activity may provide a much-needed boost (27). Beyond chromatin accessibility, it is now clear that the three-dimensional structure of AgR loci plays an important role in facilitating long-range recombination, including V to DJ H (28,29).…”
Section: Preparing Targets For V(d)j Recombinase: Transcription Pavesmentioning
confidence: 99%